2013
DOI: 10.1109/ted.2013.2282712
|View full text |Cite
|
Sign up to set email alerts
|

Ge-on-Si Single-Photon Avalanche Diode Detectors: Design, Modeling, Fabrication, and Characterization at Wavelengths 1310 and 1550 nm

Abstract: The design, modeling, fabrication, and characterization of single-photon avalanche diode detectors with an epitaxial Ge absorption region grown directly on Si are presented. At 100 K, a single-photon detection efficiency of 4% at 1310 nm wavelength was measured with a dark count rate of ∼6 megacounts/s, resulting in the lowest reported noiseequivalent power for a Ge-on-Si single-photon avalanche diode detector (1 × 10 −14 WHz −1/2 ). The first report of 1550 nm wavelength detection efficiency measurements with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 31 publications
0
78
1
Order By: Relevance
“…Following the refinement of the seed layer approach to Ge absorption layer/Si multiplication layer SPADs, there have been several experimental demonstrations of this structure. In 2013, Warburton et al demonstrated the lowest reported (to date) noise-equivalent power for a thick Ge-on-Si SPAD at 1  10 À14 WHz À½ at a wavelength of 1.31 μm [66]. The structure of this device is shown in Fig.…”
Section: à16mentioning
confidence: 94%
See 1 more Smart Citation
“…Following the refinement of the seed layer approach to Ge absorption layer/Si multiplication layer SPADs, there have been several experimental demonstrations of this structure. In 2013, Warburton et al demonstrated the lowest reported (to date) noise-equivalent power for a thick Ge-on-Si SPAD at 1  10 À14 WHz À½ at a wavelength of 1.31 μm [66]. The structure of this device is shown in Fig.…”
Section: à16mentioning
confidence: 94%
“…6 A cross section through the 25 μm diameter circular mesa structure of a germanium on silicon (Ge-on-Si) single-photon avalanche diode (SPAD) [66]. The Ni/Al layer forms the top contacts and Si3N4 is used for passivation and insulation (heterostructures) with the same crystal axis [74].…”
Section: Quantum Dot-based Detectorsmentioning
confidence: 99%
“…There is hope, though, that one day a detector such as the vertically coupled germanium APD demonstrated by Warburton et al [75] (shown in Figs. 8c and 8d) could fill the role, with sufficient performance.…”
Section: Single-photon Detectorsmentioning
confidence: 99%
“…A batch of SNSPDs is fabricated on a Si 3 N 4 membrane, selected based on performance, and transferred onto a silicon waveguide for use. c. Cross-section view of a vertically-coupled germanium avalanche photodiode from[75], and d. electron micrograph of the fabricated device. Image credit: N. C. Harris, G. S. Buller.…”
mentioning
confidence: 99%
“…It has a direct bandgap (Γ-valley) which is only 140 meV larger than the indirect bandgap, allowing for the potential of emitters such as lasers [3,4] and LEDs [5], as well as waveguides [6], photodetec-tors [7,8], and modulators [9,10], all on a Si platform. With high degenerate n-type doping the Fermi level can be moved near to the Γ-valley, resulting in either optically or electrically injected carriers having a higher probability of recombining radiatively at this band; both electrically and optically pumped Ge lasers have been demonstrated by this technique [3,4].…”
Section: Introductionmentioning
confidence: 99%